Effect of Using Micropalm Oil Fuel Ash as Partial Replacement of Cement on the Properties of Cement Mortar. (14th November 2018) - Wi, Kwangwoo; Lee, Han-Seung; Lim, Seungmin; Ismail, Mohamed A.; Hussin, Mohd Warid
Abstract : This study investigates the effects of micropalm oil fuel ash (mPOFA) on compressive strength and pore structure of cement mortar. Various experimental techniques, such as compression test, isothermal calorimetry, mercury intrusion porosimetry, and X-ray diffraction, are performed to figure out the effect of using mPOFA as partial replacement of cement on the hydration of cement and determine its optimal replacement level to increase mechanical property of the mortar specimens. 10 wt.% of cement replacement with mPOFA is found to give the highest level of compressive strength, achieving a 23% increase over the control specimens after 3 days of curing. High K2 O contents in mPOFA stimulate C3 S in cement to form C-S-H at early ages, and high surface area of mPOFA acts as a nucleus to develop C-S-H. Also, small mPOFA particles and C-S-H formed by pozzolanic reaction fill the pores and lead to reduction in large capillary pores. In XRD analysis, a decrease in Ca(OH)2 and SiO2 contents with age confirmed a high pozzolanic reactivity of mPOFA.